Monitoring of the species composition and number of insects and mites on the apple trees in the Right Bank Forest Steppe of Ukraine - Vlasova, O.; Zatserkliana, M.; Vlasova, M.; Serdiukova, M. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2024)
Goal. To monitor the species composition and abundance of insects and mites on apple trees in the Right-Bank Forest-Steppe of Ukraine. Methods. Field, laboratory, microscopic, mathematical, statistical and calculation methods. The research was carried out according to generally accepted methods in entomology and plant protection, starting in early spring (late April — early May before harvest). Results. Monitoring of the number of insect pests and mites on apple trees in three types of plantations was carried out: a young orchard on stunted rootstocks with an intensive protection system; an old orchard on tall rootstocks with a protection system; an old orchard without treatments (long-term control). Conclusions. Monitoring of species composition and dynamics of pests number makes it possible to study and substantiate the patterns in the structure of insect and mite populations, to predict their harmfulness and to improve the protection system of apple trees or its individual components.